Laparoscopically Assisted Anorectoplasty Using Perineal Ultrasonographic Guide (Journal of Paediatric Surgeons of Bangladesh, 2014)
Background/Purpose : As minimal invasive surgery,laparoscopy assisted anorectal pull-through has been reported with new devices. However, it is not easy to create an accurate pull-through canal (PTC), because of the narrow space between the urethra and puborectal sling. The authors describe a new method employing perineal ultrasonography.Methods: The rectourethral prostatic fistula was dissected laparoscopically. Externally, electrostimulation identified the center of the muscle contraction, over which a 1.2 cm of skin incision was made, and the lower part of PTC was created by hemostat forceps guided by electrostimulation. An ultrasonographic probe applied to the perineum demonstrated the urethra, and the forceps was advanced behind the urethra into the pelvic cavity using the ultrasonographic guide. Anorectal pullthrough was performed following dilatation of the PTC with dilators.Results: The authors applied this procedure in 9 cases of male high  anomalies. Surgical damages to the urethra, the levator and vertical muscles were not encountered. Postoperative MRI demonstrated a good location of the rectum, and fluoroscopic study showed a good anterior angulation and intact contraction and relaxation of those muscles.Conclusion: The combination of laparoscopic dissection, pinpointing the center of anal sphincter by electrostimulation and identification of the urethra by ultrasonographic images from the perineum facilitated creation of appropriate PTC in the muscle complex.DOI: http://dx.doi.org/10.3329/jpsb.v1i1.19447